Integration of traditional dispute resolution into Kenya’s criminal justice system: a proportionality perspective - Wokabi, D. M. (Strathmore University, 2024)
This dissertation explores the intricate balance linking the right to life and the right to culture within the framework of Traditional Dispute Resolution Mechanisms (TDRMs) in the criminal justice system of Kenya. The Constitution of Kenya, 2010, recognizes and shields the right to culture, allowing for the application of TDRMs in resolving felonies. However, concerns arise regarding the potential violation of the proportionality principle, especially in cases involving serious crimes like murder. Despite the historical resilience of TDRMs, questions arise about their compatibility with contemporary legal standards and the conservation of rudimentary liberties. The study starts by exploring origins of TDRMs and highlighting their importance in African communities' pre-colonial dispute resolution. It recognizes the constraints imposed by the declaration of Rights and emphasizes the constitutional protections of cultural rights. Pre-trial custody issues and case backlogs have been helped by the Criminal Procedure Code's provisions, especially those pertaining to reconciliation for non-felony offences. However, when TDRMs are utilized in place of the official criminal justice system for major offences, there may be a risk to the right to life, which is a fundamental human liberty. The dissertation undertakes a critical analysis of court rulings, in which the use of TDRMs led to the withdrawal of murder prosecutions. It finds a pattern in which the severity of the punishment administered by TDRMs is not commensurate with the offence committed, leading to unfair practices. Utilizing global human liberties documents, including the European Convention on Human Rights, the research delves into the notion of proportionality when establishing penalties for felonies. The study employs a qualitative methodology, relying on primary sources like the Constitution of Kenya 2010 and judgments. A comparative analysis is also employed to look at the formalisation of TDRMs and their incorporation into the justice system in Kenya by looking at the Gacaca courts in Rwanda. This study recommends the institutionalisation of TDRMs and proper integration into the criminal law realm. The conclusions drawn will guide future considerations on the appropriateness of incorporating TDRMs in the resolution of serious criminal offenses while ensuring the preservation of constitutional rights and principles of justice.
Full - text undergraduate research project